A Glance Into the Online World of Children: A study to Examine the Online Activities of Children in Indonesia - Muller, Karen; Dionisio, Astrid Gonzaga; Park, Sanghyun; Nahar; Purwianti, Ciput (Indonesian Social Work Consortium (ISWC), 2024)
Digital technology has influenced children's lives, shaping their norms, attitudes, and behaviours. This study aims to understand the online behaviours of children in Indonesia, exploring their activities, risks, and safety measures. Conducting semi-structured interviews with 510 children aged 9-18 across Central Java, East Java, and South Sulawesi Provinces in Indonesia, the study sheds light on the prevalence of internet usage among children and their online experiences. Indonesian children use the internet extensively for entertainment, communication, and information. Children consider the internet an important part of their lives, although they often lack awareness of online dangers and what constitutes risky behaviours, such as adding unknown contacts and sharing personal information, especially in online gaming contexts. Children rely on simple safety measures, necessitating comprehensive education on online safety. While many share their online experiences mainly with friends, those with strong parental bonds share it with their families too. The study emphasizes the importance of discussing online risks, including sexual exploitation and abuse, and cyberbullying as they frequently encounter such experiences but hesitate to report them. Overall, the study provides valuable insights for tailoring online safety programmes to meet children's needs and underscores the importance of informed digital parenting strategies to safeguard children's online well-being.